Global Reprogramming of Gene Transcription in Trichoderma reesei by Overexpressing an Artificial Transcription Factor for Improved Cellulase Production and Identification of Ypr1 as an Associated Regulator - Zhang, Fei; Li, Jia-Xiang; Champreda, Verawat; Liu, Chen-Guang; Bai, Feng-Wu; Zhao, Xin-Qing (Frontiers in Bioengineering and Biotechnology, 2020)
Synthetic biology studies on filamentous fungi provides unprecedented opportunities for optimizing this important category of microbial cell factories. Artificial transcription factor can be designed and used to offer novel modes of regulation on gene transcription network. Trichoderma reesei is commonly used for cellulase production. In our previous studies, an artificial zinc finger protein (AZFP) library was constructed and T. reesei strains with improved cellulase production were selected. However, the underlying mechanisms by which AZFP functions remain unclear. In this study, T. reesei mutant strain U5 bearing an AZFP U5 (AZFP-U5) was focused, which secretes more proteins and showed significantly higher cellulase and xylanase production than its parental strain T. reesei Rut-C30. Comparative transcriptomic analysis showed enhanced transcription and post-translational modifications of glycoside hydrolases and reprogramming of global gene transcription by AZFP-U5. Furthermore, 15 candidate regulatory genes which showed remarkable elevation in transcription level by AZFP-U5 insertion were overexpressed in T. reesei Rut-C30 to reveal novel regulators for cellulase biosynthesis. Overexpression of two putative regulatory genes TrC30_93861 (ypr1) and TrC30_74374 led to slightly higher FPase activity of the mutant strains than that of T. reesei Rut-C30, but deletion of these two genes did not affect cellulase activity. In addition, enhanced yellow pigment production in T. reesei Rut-C30 by overexpression of gene TrC30_93861 (ypr1) was observed, and changes of cellulase gene transcription were observed by ypr1 deletion. The results in this study revealed novel candidate genes and processes for further synthetic biology design and metabolic engineering of T. reesei to enhance cellulase production.